2015
DOI: 10.21273/hortsci.50.10.1486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Timing and Intensity of Summer Pruning on Reproductive Traits of Two Southern Highbush Blueberry Cultivars

Abstract: Blueberry (Vaccinium spp.) summer pruning can increase yield by promoting healthy fall foliage to support the reproductive development. However, there has been little research to examine the effects of timing and intensity of summer pruning in subtropical conditions. The objective of this study was to determine the effects of summer pruning timing and intensity on reproductive traits of mature ‘Jewel’ and ‘Emerald’ southern highbush blueberry (SHB) plants (V. cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…The high levels of Ca and bicarbonate found in the irrigation water in Archer, combined with the transient increase in soil pH (6.0-6.3) from Feb. to July 2013, decreased plant growth, particularly in nonamended soils. The reduced canopy volume may decrease availability of carbohydrates for fruit development (Maust et al, 1999), potentially decreasing berry weight, supporting work by Kovaleski et al (2015), who reported reduction in mean berry weight in plants that had 60% of the canopy removed compared with nonpruned plants.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The high levels of Ca and bicarbonate found in the irrigation water in Archer, combined with the transient increase in soil pH (6.0-6.3) from Feb. to July 2013, decreased plant growth, particularly in nonamended soils. The reduced canopy volume may decrease availability of carbohydrates for fruit development (Maust et al, 1999), potentially decreasing berry weight, supporting work by Kovaleski et al (2015), who reported reduction in mean berry weight in plants that had 60% of the canopy removed compared with nonpruned plants.…”
Section: Discussionsupporting
confidence: 61%
“…Mean berry weight varied considerably between field locations and cultivars. Previous work report differences in mean berry weight due to different factors, such as pruning (Kovaleski et al, 2015), seed number per berry (Harrison et al, 1993), source:sink ratio (Maust et al, 1999), and pollination (Bell et al, 2010). In Citra, differences in mean berry weight were cultivar dependent.…”
Section: Discussionmentioning
confidence: 96%
“…One of the first available in the market, the Emerald cultivar is a southern highbush blueberry selected by University of Florida (Florida, USA) for its low cold requirement (temperatures below 7.2°C), early production, and large fruit size. When grown in Florida, its harvest extends from mid-April to mid-May (Kovaleski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Summer pruning consists of cutting back shoots during the plant's active growth period from early summer through autumn to reduce the height of the bush and to stimulate branching and flower bud formation. However, most of the summer pruning studies on blueberries have been done in Chile and the United States (Bañados et al, 2009;Jorquera et al, 2014;Kovaleski et al, 2015a, b), where agroclimatic and management conditions are far different from those in the Japanese blueberry production areas. Müller (2011) found that summer pruning increased berry weight and diameter by reducing the total yield of the southern highbush blueberry in Stellenbosch, South Africa.…”
Section: Introductionmentioning
confidence: 99%